The גר who wasn't there: Fictional Aliens in the Damascus Rule - Moynihan Gillihan, Yonder (2011)
The several sectarian texts from among the DSS that contain references to גרים pose significant problems for the historian. How should we translate the term - 'permanent resident alien', as in Scripture, or 'Gentile proselyte', as in rabbinic literature? Why do some texts, such as the Damascus Rule and 4QLots, treat the גר positively, while others, such as 4QFlorilegium, are entirely hostile to them? In view of the sect’s general rejection of outsiders, especially Gentiles, in texts such as the War Rule and 4QMMT, how can the positive references to גרים be explained? Widely varying solutions have been proposed, all of which assume that the term גר designates a real social group within the sect. This essay tentatively proposes an alternative thesis: while גר seems to designate Gentile converts in sectarian texts, the category is a legal fiction created on the basis of Scripture - it seems highly unlikely that Gentiles ever joined the sect. Positive portraits of גרים in sectarian texts come from interest in crafting halakah for the pre-eschatological age that reflects scriptural law as faithfully as possible. Since throughout Scripture the גר is portrayed as participating in Israelite assemblies, cultic worship, and juridical activity, and since numerous laws protect them from abuse and guarantee their access to material support when in need, the laws of D and other texts provide for similar inclusion. The Covenanters also thought of the גר ’s inclusion as temporary: eschatologically oriented texts show anticipation that the land, people, and cult of Israel would be purged entirely of Gentiles, including 'good' גרים. This purge of Gentiles would at last fulfill God’s command to Moses, to rid the land of idolatrous peoples. My proposal describes a consistent, if complex, attitude toward גרים in all sectarian texts that treat them. It also highlights the complexity of the Covenanters’ halakah: some laws were intended to be followed in the present but not in restored Israel; others could not be followed at all in the present but would be at the restoration; still others could be followed partially now, but only fully with restoration. A few laws could neither be followed in the present nor in restored Israel, but had to be included in sectarian halakah due to the recurrence of their themes throughout Scripture. In this last category are laws that treat גרים positively.\n4207 \n4207